Do digital devices enhance teenagers’ recreational reading engagement? Issues for library policy from a recent study in two Australian states - Rutherford, L.; Singleton, A.; Derr, L.; Merga, Margaret (Routledge, 2018)
©, Published with license by Taylor & Francis. © Leonie Rutherford, Andrew Singleton, Leonee Ariel Derr and Margaret Kristin Merga. ©, © Leonie Rutherford, Andrew Singleton, Leonee Ariel Derr and Margaret Kristin Merga. Digital platforms have become central to twenty-first century education, culture, and government, and libraries devote an increasing proportion of budgets to acquisitions of e-resources. This research reports on a recent project that investigated Australian teenagers’ use of traditional print and digital platforms for long-form recreational reading. Specifically, it investigates whether digital devices are a preferred modality for Australian adolescents’ recreational reading and if access to digital devices with e-reading capabilities, such as tablets, smartphones, e-readers, and laptop or desktop computers, is associated with more reading engagement by avid and reluctant readers. The research, based on a diverse sample of urban and regional participants from two states, suggests that Australian adolescents’ preferences for e-books have been largely overestimated. Issues of relevance to public libraries are discussed.